تأثير استخدام فطر البيـري ((Piriformospora indica كمخصب حيوي في نمو وإزهار ومعامل التكاثر لنبات سيف الغراب (Gladiolus hybrida) (Latakia University Journal -Biological Sciences Series, 2018)
The present investigation was carried out in Agricultural Scientific research Center -Lattakia, during 2015-2016, to evaluate the best method and date of inoculation by Piriformospora indica on vegetative growth, flowering, corms and cormels production of Gladiolus (Gladiolus hybrida).  The experiment was laid out in Randomized Block Design with three replications and six treatments:(T0: control , T1: organic fertilizer,T2: organic fertilizer + steeping corms  in  P. indica 2 hours before planting, T3: organic fertilizer+ irrigation by P. indica suspension,T4: organic fertilizer + steeping corms+ irrigation by P. indica and T5: steeping corms + irrigation by P. indica. The results showed that the use of p. indica had a positive impact on vegetative growth (plant height and average number of leaves / plant, proportion of dry matter), in addition it showed a positive effect on the formation of Spikes and flowering (early flowering, spike length, number of florets per spike and thickness of spike at basal floret). The yield of corms/plant was significantly increased in response to p. indica in presence of organic fertilizer and produced higher cormels yield than the control and organic fertilizer treatments. Data Showed that T2 treatment realized higher economic profit than other treatments (127.9%). نفذ البحث في مركز البحوث العلمية الزراعية- اللاذقية لعامي 2015-2016 لتحديد أفضل طريقة وموعد للمعاملة بفطر البيري Piriformospora indica)) بدراسة بعض مؤشرات النمو الخضري والزهري لنبات سيف الغراب (Gladiolus hybrida). صممت التجربة بطريقة القطاعات العشوائية الكاملة بـ 6 معاملات وثلاث مكررات: (T0) شاهد، (T1) تسميد عضوي، (T2) تسميد عضوي مع نقع الكورمات بمعلق الفطر لمدة 2 ساعة قبل الزراعة، (T3) تسميد عضوي ثم السقي بمعلق الفطر،  (T4)تسميد عضوي مع النقع والسقي بمعلق الفطر، (T5) أرض التجربة مع النقع والسقي بمعلق الفطر. أظهرت النتائج أن لفطر البيري أثراً إيجابياً على مؤشرات النمو الخضري سواءً مع التسميد العضوي أو بدونه (طول النبات، متوسط عدد الأوراق، نسبة المادة الجافة). إضافة لتأثيره على تشكيل الشماريخ الزهرية وتطورها (التبكير في الإزهار، طول الشماريخ، عدد الأزهار على الشمراخ، ثخانة الشمراخ عند الزهرة القاعدية، نوعية الشماريخ). سجلت معاملات النقع بالفطر تبكيراً بالإزهار وصل حتى 7 أيام. ساهم التسميد الحيوي بفطر البيري بوجود السماد العضوي بزيادة وبفروق معنوية في عدد الكورمات /النبات وقطر الكورمة الأم، كما حقق الفائدة الاقتصادية المعنوية، إذ حققت معاملة نقع الكورمات بالفطر (T2) أعلى معامل ربحية مقارنةً بجميع المعاملات الأخرى (127,9%).